Reducing falls among older people in general practice: the ProAct65+ exercise intervention trial - Gawler, Sheena; Skelton, Dawn A.; Dinan-Young, Susie; Masud, Tahir; Morris, Richard W.; Griffin, Mark; Kendrick, Denise; Iliffe, Steve (Elsevier, 2016)
Background: Falls are common in the older UK population and associated costs to the NHS are high. Systematic reviews suggest that home exercise and group-based exercise interventions, which focus on progressively challenging balance and increasing strength, can reduce up to 42% of falls in those with a history of falls. The evidence is less clear for those older adults who are currently at low risk of falls. Aim: ProAct65+, a large, cluster-randomised, controlled trial, investigated the effectiveness of a home exercise programme (Otago Exercise Programme (OEP)) and a group-based exercise programme (Falls Management Exercise (FaME)) compared to usual care (UC) at increasing moderate to vigorous physical activity (MVPA). This paper examines the trial’s secondary outcomes; the effectiveness of the interventions at reducing falls and falls-related injuries. Setting & participants: 1256 community-dwelling older adults (aged 65 + ) were recruited through GP practices in two sites (London and Nottingham). Frequent fallers (≥3 falls in last year) and those with unstable medical conditions were excluded, as were those already reaching the UK Government recommended levels of physical activity (PA) for health. Methods: Baseline assessment (including assessment of health, function and previous falls) occurred before randomisation; the intervention period lasted 24 weeks and there was an immediate post-intervention assessment; participants were followed up every six months for 24 months. Falls data were analysed using negative binomial modelling. Outcome measures: Falls data were collected prospectively during the intervention period by 4-weekly diaries (6 in total). Falls recall was recorded at the 3-monthly follow-ups for a total of 24 months. Balance was measured at baseline and at the end of the intervention period using the Timed Up & Go and Functional Reach tests. Balance confidence (CONFbal), falls risk (FRAT) and falls self-efficacy (FES-I) were measured by questionnaire at baseline and at all subsequent assessment points. Results: 294 participants (24%) reported one or two falls in the previous year. There was no increase in falls in either exercise group compared to UC during the intervention period (resulting from increased exposure to risk). The FaME arm experienced a significant reduction in injurious falls compared to UC (incidence rate ratio (IRR) 0.55, 95% CI 0.31, 0.96; p = 0.04) and this continued during the 12 months after the end of the intervention (IRR 0.73, 95% CI 0.54, 0.99; p = 0.05). There was also a significant reduction in the incidence of all falls (injurious and non-injurious) in the FaME arm compared with UC (IRR 0.74, 95% CI 0.55, 0.99; p = 0.04) in the 12 month period following the cessation of the intervention. There was a non-significant reduction in the incidence of all falls in the OEP arm compared with UC (IRR 0.76, 95% CI 0.53, 1.09; p = 0.14) in the 12 months following the cessation of the intervention. The effects on falls did not persist at the 24 months assessment in either exercise arm. However, when those in the FaME group who continued to achieve 150 min of MVPA per week into the second post-intervention year were compared to those in the FaME group who did not maintain their physical activity, there was a significant reduction in falls incidence (IRR = 0.49, 95% CI 0.30, 0.79; p = 0.004). CONFbal was significantly improved at 12 months post intervention in both intervention arms compared with UC. There were no significant changes in any of the functional balance measures, FES-I or FRAT, between baseline and the end of the intervention period. Conclusion: Community-dwelling older adults who joined an exercise intervention (FaME) aimed at increasing MVPA did not fall more during the intervention period, fell less and had fewer injurious falls in the 12 months after cessation of the intervention. However, 24 months after cessation of exercise, the beneficial effects of FaME on falls reduction ceased, except in those who maintained higher levels of MVPA. OEP exercise appears less effective at reducing falls in this functionally more able population of older adults.